Evaluation of Pharmacogenetic Algorithm for Warfarin Dose Requirements in Japanese Patients - Takeuchi, Fumihiko; Hiroe, Michiaki; Kashida, Mitsuo; Kashima, Toshitaka; Fukuda, Shoji; Tanaka, Yuriko; Hosaka, Shigeru; Kimura, Sosuke; Kato, Norihiro; Okazaki, Osamu (Circulation Journal, 2010)
Background: Warfarin dosing is difficult to establish because of considerable interindividual variation. Thus, warfarin pharmacogenetics have attracted particular interest in relation to appropriate control of anticoagulation. Methods and Results: The 200 eligible subjects were chosen from participants in a hospital cohort. Performance of a pharmacogenetic algorithm recently developed by the International Warfarin Pharmacogenetics Consortium (IWPC) was tested and compared with a clinical algorithm (without genotype data) by calculating the percentage of patients for whom the predicted dose deviated by less than 7 mg/week (1 mg/day) from the actual dose. The pharmacogenetic algorithm accurately identified a significantly (P<0.05) larger proportion of patients to achieve the target international normalized ratio than did the clinical algorithm (68% vs 36% for a low-dose group; and 21% vs 0% for a high-dose group). Also, an increase in warfarin dosage was found to be appropriate for the current status of alcohol drinking (4 mg/week, as against non-drinking) and smoking (3.3 mg/week, as against non-smoking). Conclusions: The IWPC pharmacogenetic algorithm has clinical application, particularly in identifying Japanese patients who require a low dosage of warfarin and are at greater risk of excessive anticoagulation. (Circ J 2010; 74: 977 - 982)